Against the Received Wisdom: Why Should the Criminal Justice System Give Kids a Break? - Morse, Stephen J. (2019)
Professor Gideon Yaffe’s recent, intricately argued book, The Age of Culpability: Children and the Nature of Criminal Responsibility, argues against the nearly uniform position in both law and scholarship that the criminal justice system should give juveniles a break not because on average they have different capacities relevant to responsibility than adults, but because juveniles have little say about the criminal law, primarily because they do not have a vote. For Professor Yaffe, age has political rather than behavioral significance. The book has many excellent general analyses about responsibility, but all are in aid of the central thesis about juveniles, which is the central focus of this essay review. After addressing a few preliminary issues, the essay discusses Professor Yaffe’s negative argument against the validity of the behavioral difference rationale for giving juveniles a break. If the negative case fails, which the essay argues it does, then the only issue is whether the book’s alternative is desirable. Again, the essay argues that it is not, and concludes by offering three positive arguments for the traditional rationale: 1) coherence and simplicity; 2) a benignly definitional argument that survives the negative argument and supports giving juveniles a break in the exceedingly unlikely event that the empirical assumptions of the traditional rationale are proven incorrect; and 3) a proposal for individualization of the culpability assessments of juveniles so that the criminal justice system blames and punishes them proportionately to their culpability